Strategi Efektif Guru dalam Mengimplementasikan Sekolah Inklusi pada Lembaga PAUD - Latifah, Ibdaul; Fadila, Winda Noor (Al Athfal : Jurnal Kajian Perkembangan Anak dan Manajemen Pendidikan Usia Dini, 2024)
Inclusive schools are one of the main focuses of education policy in many countries, including Indonesia. The implementation of inclusive schools has experienced various kinds of problems and difficulties. These problems are also felt by teachers in early childhood education institutions. Teachers agree with the implementation of inclusive schools, but in implementing them they face various kinds of problems. This research aims to describe the problems faced by teachers in implementing inclusive schools and tries to provide effective strategies in dealing with these difficulties. This research uses a descriptive qualitative approach with data collection techniques in the form of interviews, observation and documentation. The interview technique used was a semi-structured interview. Source triangulation and techniques are used to check the validity of the data. The research location in TK Al Qudwah Kids Center, Salatiga. The results of the research are that the problems faced by teachers in implementing inclusive schools are the lack of knowledge about inclusive education, parents not wanting to be open with the true condition of their children, and inadequate facilities and infrastructure. Given these problems, teachers look for strategies to overcome them by conducting initial screening on students, collaborating with psychologists, frequently communicating with parents, and attending seminars and training on inclusive education.